Pengaruh Kepemimpinan Intruksional Kepala Madrasah dan Komitmen Kerja Terhadap Kinerja Guru Madrasah Tsanawiyah Kabupaten Agam - Reni Arneti; Hadiyanto; Sulastri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Instructional leadership and work commitment are things that school principals must have. Teachers have an important role in education. Teacher performance also needs to be improved. Principals play an important role in shaping schools, especially in encouraging higher levels of institutional independence. The purpose of writing this article is to analyze the influence of the madrasa head's instructional leadership and work commitment on the performance of Madrasah Tsanawiyah teachers in Agam Regency. The research used by the author is Systematic Literature Review (SLR) with the PRISMA (Preferred Reporting Items for Systematic Review and Meta Analysis) method. The data used in this research is secondary data originating from national scientific articles in the period 2020 to 2024. The database used is Google Scholar. The keywords used are work commitment, leadership, teacher performance. The results of this research are: The results of this research show 15 articles that show a positive relationship between instructional leadership and work commitment to performance. The conclusion is that instructional leadership and work commitment influence performance, where the better the application of leadership and commitment to the organization, the more performance will improve. This relationship indicates that factors such as good leadership and high work commitment play a crucial role in maximizing individual and team performance in the organization.